Furanoid F-Acid F6 Uniquely Induces NETosis Compared to C16 and C18 Fatty Acids in Human Neutrophils - Meraj A. Khan (Biomolecules, 2018)
Various biomolecules induce neutrophil extracellular trap (NET) formation or NETosis. However, the effect of fatty acids on NETosis has not been clearly established. In this study, we focused on the NETosis-inducing ability of several lipid molecules. We extracted the lipid molecules present in Arabian Gulf catfish (Arius bilineatus, Val) skin gel, which has multiple therapeutic activities. Gas chromatography–mass spectrometry (GC-MS) analysis of the lipid fraction-3 from the gel with NETosis-inducing activity contained fatty acids including a furanoid F-acid (F6; 12,15-epoxy-13,14-dimethyleicosa-12,14-dienoic acid) and common long-chain fatty acids such as palmitic acid (PA; C16:0), palmitoleic acid (PO; C16:1), stearic acid (SA; C18:0), and oleic acid (OA; C18:1). Using pure molecules, we show that all of these fatty acids induce NETosis to different degrees in a dose-dependent fashion. Notably, F6 induces a unique form of NETosis that is rapid and induces reactive oxygen species (ROS) production by both NADPH oxidase (NOX) and mitochondria. F6 also induces citrullination of histone. By contrast, the common fatty acids (PA, PO, SA, and OA) only induce NOX-dependent NETosis. The activation of the kinases such as ERK (extracellular signal-regulated kinase) and JNK (c-Jun N-terminal kinase) is important for long-chain fatty acid-induced NETosis, whereas, in F-acid-induced NETosis, Akt is additionally needed. Nevertheless, NETosis induced by all of these compounds requires the final chromatin decondensation step of transcriptional firing. These findings are useful for understanding F-acid- and other fatty acid-induced NETosis and to establish the active ingredients with therapeutic potential for regulating diseases involving NET formation.